PENGARUH DOMINAN CURRENT RATIO, DEBT TO ASSET RATIO, TOTAL ASSETS TURNOVER TERHADAP RETURN ON EQUITY PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Yuniastuti, Rina Milyati (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2017)
The Purpose of this research is to be achieved is to determine the most dominant inï¬uence between current ratio, debt to assets ratio, total asset turnover, and return on equity to food and beverage companies on the stock exchange Indonesia. In the study to provide information will be the dominant inï¬uence between current ratio, debt to asset ratio, total asset turnover to return on equity useful for investor. And in the research the dominant inï¬ uence is total asset turnover.